Comparison of Trucking Service Platform: A Qualitative Research - Failui, Nantiya; Kiatpanont, Rangsan (Rajapark Journal, 2021)
The objective of this research is to compare trucking service platforms. And recommending qualitative research, we collected data interviewed with 60 platform users from three sources: information from related websites. Interview data for 30 carrier-side platform users and 30 carrier-client platform users using Data Triangulation using Content Analysis. To extract information related to research objectives and present the results of the data analysis by descriptive methods. The research reveals that operator users will pay more attention to how the platform generates additional revenue. On the other hand, customers tend to focus more on value for money and service quality. In addition, users on both sides expect a platform that is easy to use, stable, and easy to contact customer support when having problems. By comparing the platforms, it was found that The Giztix platform stands out from other platforms in terms of the amount of workload. While the Deliveree platform has a more flexible process on the carrier side. As for the Pan-truck platform, it has the advantage that customers can talk to service providers directly. And the service user is the one who determines the price mainly. As a result, transportation services in Pan Truk are low in price. This can be summarized as a guideline for developing the platform. To improve service quality in 4 areas: 1) the consistency of the workload in the platform 2) the application system is easy to use and stable. 3) Easier to contact customer service 4) Building understanding among platform users about service quality.